ENFERMEDAD LINFOPROLIFERATIVA EN LA COLUMNA: FACTORES PREDICTIVOS DE COMPLICACIÓN POSTOPERATORIA - RAFAEL MORAES TRINCADO; JORGE RAFAEL DURIGAN; FELIPE NEVES SIMÕES MONTEIRO; JOÃO TOMÁS FERNANDES CASTILHO GARCIA; MURILO ALEXANDRE; RODRIGO GÓES MEDEA DE MENDONÇA; ALBERTO OFENHEJM GOTFRYD; MARIA FERNANDA SILBER CAFFARO; ROBERT MEVES (Coluna/Columna)
ABSTRACT Objectives: This study aimed to analyze predictive factors for postoperative complications in patients with lymphoproliferative disease in the spine. Materials and Methods: An observational retrospective study was conducted at a quaternary service between 2017 and 2021. Postoperative complications, 1-year survival, and correlations with Karnofsky, SINS, and ASIA scales were evaluated. Results and Discussion: Of the 23 participants, 21.7% experienced postoperative complications, with laminectomy + arthrodesis being the most common procedure. Patients with lower Karnofsky scores showed a higher incidence of complications, while 1-year survival was 60%, which is correlated with preoperative functionality. Factors such as Karnofsky and ASIA are relevant for predicting complications and survival. Patients with preoperative functional impairment had worse outcomes, corroborating previous studies. Conclusion: Multifactorial evaluation, including Karnofsky and ASIA, is essential for planning the treatment of patients with lymphoproliferative disease in the spine, aiming to reduce postoperative complications and improve survival. Level of Evidence IV; Observational Retrospective Study.